Propagating Waves in Human Motor Cortex - Takahashi, Kazutaka; Saleh, Maryam; Penn, Richard D.; Hatsopoulos, Nicholas (Frontiers in Human Neuroscience, 2011)
Previous studies in non-human primates have shown that beta oscillations (15-30Hz) of local field potentials (LFPs) in the arm/hand areas of primary motor cortex (MI) propagate as traveling waves across the cortex. These waves exhibited two stereotypical features across animals and tasks: 1) The waves propagated in two dominant modal directions roughly 180 degrees apart, and 2) their propagation speed ranged from 10 ~ 35 cm/s. It is, however, unknown if such cortical waves occur in the human motor cortex. This study shows that the two properties of propagating beta waves are present in MI of a tetraplegic human patient while he was instructed to perform an instruction delay center out task using a cursor controlled by the chin. Moreover, we show that beta waves are sustained and have similar properties whether the subject was engaged in the task or at rest. The directions of the successive sustained waves both in the human subject and a nonhuman primate (NHP) subject tended to switch from one dominant mode to the other, and at least in the NHP subject the estimated distance travelled between successive waves traveling into and out of the central sulcus is consistent with the hypothesis of wave reflection between the border of motor and somatosensory cortices. Further, we show that the occurrence of the beta waves is not uniquely tied to periods of increased power in the beta frequency band. These results demonstrate that traveling beta waves in MI are a general phenomenon occurring in human as well as non-human primates. Consistent with the non-human primate data, the dominant directions of the beta LFP waves in human aligned to the proximal to distal gradient of joint representations in MI somatotopy. This consistent finding of wave propagation may imply the existence of a hardwired organization of motor cortex that mediates this spatio-temporal pattern.